A study on the spatio-temporal characteristics of wastewater in Phnom Penh, Cambodia for the development of a treatment system - Lim, Sopheap
This study presents the spatio-temporal characterization of wastewater discharging into the Trabek Lake located in the southern part of Phnom Penh City,Cambodia necessary for the design of a wastewater treatment plant. Results of a questionnaire survey on the willingness of residents on wastewater treatment payment are also presented in this study. The Storm Water Management Modeling (SWMM) was used to predict the spatiotemporal characteristic of quality and quantity of wastewater and Geographic Information System (GIS) was utilized to incorporate the effect of land use on wastewater. Biological oxygen demand (BOD), chemical oxygen demand (COD) and total phosphate (PO4) were measured at the exit of subcatchments and these parameters were used for the calibration and validation of the model. The accuracy of adjustment of the discharge during wet and dry season was 84% and 82%. The discharge validation of wet season was 83%. As for the quality calibration, the accuracy of adjustment of BOD, COD and PO4 of wet seasons was 88.75%, 82.31% and 81.08% respectively. For dry weather, the quality calibration of BOD =85.07%, COD=86.88% and PO4=87.51% respectively. Based on simulated and observed data, it reveals that all the three parameters such as BOD, COD and PO4 are Exceedance standard of Environmental sub-decree of Cambodia.The results from questionnaire survey revealed that 46% of respondents agree to have wastewater treatment plant and are willing to pay 10-50% of their monthly bill of water consumption while 31% of them can afford only 0.238-2.38